Structure and Interaction of Poly(ethylene glycol) in Aqueous Solutions. Small‐Angle Neutron Scattering Data. Issue 1 (January 2014) - Petrenko, Viktor; Bulavin, Leonid; Avdeev, Mikhail; Garamus, Vasil; Koneracka, Martina; Kopcansky, Peter; Bulavin, Leonid; Guenet, Jean‐Michel
Summary Behavior of low molecular mass poly(ethylene glycol) (PEG) polymer, i.e. molar masses Mn = 400 and 1000, in heavy water is studied by small‐angle neutron scattering (SANS). Some part of the polymer molecules in concentrated solutions is found to form aggregates with size exceeding 30 nm. The form‐factor of Gaussian coil is used to describe low concentrated PEG solutions. Virial coefficients are obtained from approximation of experimental SANS data for PEG solutions with concentration higher than 3% where the interparticle interaction effect is well observed.